Incorporating English and Islamic Knowledge into Workbook Development for Primary School Students - Farah, Rafika Rabba; Waloyo, Alimin Adi; Sumarsono, Puji (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2021)
English teaching at primary school in Indonesia has experienced some changes in its curriculum, the K13 curriculum is the one that is implemented currently. However, there are some challenges that occur such as the time allocated for the English teaching until its textbook design. Henceforth, English teaching at primary school needs a new move. Another significant issue is related to the design of the curriculum that needs to be adjusted to each school context. In Islamic schools, English teaching finds its own issue, mainly on the cultural aspect—Western culture and ideology. Thus, this present research aims at developing an English workbook that is Muslim-friendly for their students. The method implemented in this study was Research & Development (R&D) with ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. This research has resulted that there were 5 major topics related to Islamic content developed, such as believing in Allah and Rasulullah, salah, al-Qur’an, noble characters, and the Prophets. Further, this research has resulted from a concept of workbook design, comprising brainstorming, short text, and activities that divided into three categories: cognitive activities (matching and listing), kinesthetic activities (drawing, coloring, and tracing), and the last one is vocabulary-based activity (word search and puzzle). All chapters were designed by considering the implemented curriculum at school partners. The finding of this research has shed light that integrating English and Islamic content can be a way for Islamic schools in Indonesia to build Islamic value to their students as well as to find the school's own character.